2011
DOI: 10.1016/j.jmpt.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cavitations as Identified with Accelerometry During Lumbar Spinal Manipulation

Abstract: Objective This project determined the location and distribution of cavitations (audible sounds producing vibrations) in the lumbar zygapophyseal (Z) joints that were targeted by spinal manipulative therapy (SMT). Methods This randomized, controlled, clinical study assessed 40 healthy subjects (20 male, 20 female), 18–30 years of age, that were block randomized into SMT (Group 1, n=30) or side-posture positioning only (Group 2, control, n=10) groups. Nine accelerometers were placed on each patient (7 on SPs/s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…This concept of a mechanoreceptor activation gradient is supported by biomechanical studies showing that while a majority of HVLA-SM related cavitations are typically confined to a 3 contiguous vertebra area, more distant cavitations do occur albeit with less frequency. 29,31 In addition, HVLA-SM has been shown to produce measurable in vivo intervertebral motions at remote vertebra 63 and less forceful grade IV posterior-to-anterior spinal mobilizations applied at each lumbar spinous process elicit vertebral movement at all levels of the lumbar spine as demonstrated using in vivo dynamic MRI studies. 64,65 While it remains mechanistically unclear, various theories have been proposed of how HVLA-SM mechanoreceptor stimulation could produce sustained physiological changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This concept of a mechanoreceptor activation gradient is supported by biomechanical studies showing that while a majority of HVLA-SM related cavitations are typically confined to a 3 contiguous vertebra area, more distant cavitations do occur albeit with less frequency. 29,31 In addition, HVLA-SM has been shown to produce measurable in vivo intervertebral motions at remote vertebra 63 and less forceful grade IV posterior-to-anterior spinal mobilizations applied at each lumbar spinous process elicit vertebral movement at all levels of the lumbar spine as demonstrated using in vivo dynamic MRI studies. 64,65 While it remains mechanistically unclear, various theories have been proposed of how HVLA-SM mechanoreceptor stimulation could produce sustained physiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…31 A more recent study found that only 71.7% of HVLA-SM related cavitations are confined to a 3 vertebral segment area. 29 Despite the importance typically imputed to clinically identifying the precise level of spinal joint fixation and contacting that target level for an HVLA-SM, it is not clear to what extent fixated joints (targeted) would respond differently from non-fixated joints (non-targeted) to HVLA-SM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those who passed the initial screening were scheduled for an examination where a research chiropractic physician conducted a thorough history and physical examination that included orthopedic and neurological tests to ensure subjects were selected who met stringent inclusion and had none of the exclusion criteria. Separate criteria that had been previously developed and implemented for healthy 19,20 and LBP subjects 37 were used in this study. Generally, healthy subjects had no current LBP, known spinal pathology, or spinal surgery; and no previous history of LBP lasting more than 2 weeks, or no more than 3 episodes of LBP of brief duration (one week) in any given year.…”
Section: Methodsmentioning
confidence: 99%
“…1921 This feasibility study (n=10) was designed to continue the process of addressing the current gaps of knowledge by further developing previous methods and evaluating additional methods to assess and localize Z joint crepitus recorded during lumbar motion both before and after SMT. More specifically, this study evaluated recordings made simultaneously from accelerometers and a specialized directional microphone.…”
Section: Introductionmentioning
confidence: 99%